Smart displays in Ambient Intelligence Environments - Ribeiro, Fernando Reinaldo (2015)
A public display that is able to present the right information at the right time is a very compelling concept. However, realising or even approaching this ability to autonomously select appropriate content based on some interpretation of the surrounding social context represents a major challenge. This chapter provides an overview of the key challenges involved and an exploration of some of the main alternatives available. It also describes a novel content adaptation framework that defines the key building blocks for supporting autonomous selection of the web sources for presentation on public displays. This framework is based on a place model that combines content suggestions expressed by multiple place visitors with those expressed by the place owner. Evaluation results have shown that a place tag cloud can provide a valuable approach to this issue and that people recognize and understand the sensitivity of the system to their demands.